Menu Close

2cos-x-4-cos-x-4-




Question Number 9029 by rzagung last updated on 15/Nov/16
  2cos(x+Π/4)=cos(x−Π/4)
2cos(x+Π/4)=cos(xΠ/4)
Answered by Rasheed Soomro last updated on 15/Nov/16
2cos(x+π/4)=cos(x−π/4)  cos(x+π/4)+cos(x+π/4)−cos(x−π/4)=0  cos(x+π/4)+(−2sin(((x+π/4)+(x−π/4))/2)sin(((x+π/4)−(x−π/4))/2))=0  cos(x+π/4)−2sin(x)sin(π/4)=0  cos(x)cos(π/4)−sin(x)sin(π/4)−2sin(x)sin(π/4)=0  cos(x)cos(π/4)−3sin(x)sin(π/4)=0  cos(x)(1/(√2))−3sin(x)(1/(√2))=0  cos(x)−3sin(x)=0  cos(x)=3sin(x)  ((sin(x))/(cos(x)))=(1/3)  tan(x)=(1/3)  x=tan^(−1) ((1/3))  x=nπ+tan^(−1) ((1/3))      ∀n∈Z      ( in general)
2cos(x+π/4)=cos(xπ/4)cos(x+π/4)+cos(x+π/4)cos(xπ/4)=0cos(x+π/4)+(2sin(x+π/4)+(xπ/4)2sin(x+π/4)(xπ/4)2)=0cos(x+π/4)2sin(x)sin(π/4)=0cos(x)cos(π/4)sin(x)sin(π/4)2sin(x)sin(π/4)=0cos(x)cos(π/4)3sin(x)sin(π/4)=0cos(x)(1/2)3sin(x)(1/2)=0cos(x)3sin(x)=0cos(x)=3sin(x)sin(x)cos(x)=13tan(x)=13x=tan1(13)x=nπ+tan1(13)nZ(ingeneral)
Answered by Rasheed Soomro last updated on 15/Nov/16
2cos(x+π/4)=cos(x−π/4)  cos(x+π/4)=cos(x)cos(π/4)−sin(x)sin(π/4)                           =((cos(x))/( (√2)))−((sin(x))/( (√2)))  cos(x−π/4)=cos(x)cos(π/4)+sin(x)sin(π/4)                           =((cos(x))/( (√2)))+((sin(x))/( (√2)))  2(((cos(x))/( (√2)))−((sin(x))/( (√2))))=((cos(x))/( (√2)))+((sin(x))/( (√2)))  2(cos(x)−sin(x))=cos(x)+sin(x)  cos(x)=3sin(x)  ((sin(x))/(cos(x)))=(1/3)  tan(x)=(1/3)  x=tan^(−1) ((1/3))+nπ      ∀  n∈Z
2cos(x+π/4)=cos(xπ/4)cos(x+π/4)=cos(x)cos(π/4)sin(x)sin(π/4)=cos(x)2sin(x)2cos(xπ/4)=cos(x)cos(π/4)+sin(x)sin(π/4)=cos(x)2+sin(x)22(cos(x)2sin(x)2)=cos(x)2+sin(x)22(cos(x)sin(x))=cos(x)+sin(x)cos(x)=3sin(x)sin(x)cos(x)=13tan(x)=13x=tan1(13)+nπnZ

Leave a Reply

Your email address will not be published. Required fields are marked *